2020
DOI: 10.3390/cells9102272
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Chemical Knockdown of MuRF1 in Melanoma Bearing Mice Attenuates Tumor Cachexia Associated Myopathy

Abstract: Patients with malignant tumors frequently suffer during disease progression from a syndrome referred to as cancer cachexia (CaCax): CaCax includes skeletal muscle atrophy and weakness, loss of bodyweight, and fat tissues. Currently, there are no FDA (Food and Drug Administration) approved treatments available for CaCax. Here, we studied skeletal muscle atrophy and dysfunction in a murine CaCax model by injecting B16F10 melanoma cells into mouse thighs and followed mice during melanoma outgrowth. Skeletal muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 50 publications
3
21
1
4
Order By: Relevance
“…Next, we studied the effects of the recently described small molecules that inhibit MuRF1 [ 19 , 20 , 21 ] in a mouse model for T2DM. We hypothesized that such a treatment might attenuate the myopathy accompanying T2DM by inhibiting the MuRF1 atrogene functions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we studied the effects of the recently described small molecules that inhibit MuRF1 [ 19 , 20 , 21 ] in a mouse model for T2DM. We hypothesized that such a treatment might attenuate the myopathy accompanying T2DM by inhibiting the MuRF1 atrogene functions.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the inhibition of cachexia promoting E3 ligases could be a potential treatment strategy to attenuate secondary myopathies. In line with this rationale, we recently identified MuRF1 inhibiting small molecules that slow down muscle mass and force loss in cardiac and cancer cachexia, respectively [ 19 , 20 , 21 ]. Here, we investigated if two compounds from this novel class of (2-oxo-chromen-7-yl)-heteromethyl-benzoic acids; i.e., MyoMed-205 and MyoMed-946 [ 21 ]) also have the potential to attenuate a secondary myopathy in a type 2 diabetes mellitus (T2DM) murine model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound was at least partially effective for preserving muscle mass in catabolic mice. The mechanism by which compound ID#704946/MyoMed-946 preserve muscle function needs further investigations as the same laboratory found that it was also able to modulate MuRF2 expression [ 17 , 18 ].…”
Section: Current Treatments/potential Modes Of Actionmentioning
confidence: 99%
“…Within muscle atrophy, numerous ubiquitinating enzymes are now identified for their involvement in the regulation of both anabolic and catabolic pathways during the atrophy process, notably by being responsible for the degradation of the contractile proteins [ 12 ]. The E3 Ub ligases appear to be at the heart of these regulations and some of them may prove to be efficient therapeutic drug strategies with roughly two main approaches: (i) indirect modulation of an E3 ligase by targeting the signals involved in its regulation [ 13 , 14 , 15 , 16 ] or (ii) direct inhibition of the E3 ligase [ 17 , 18 , 19 ]. However, the intertwinement between anabolic and catabolic processes (including the signaling pathways) often renders difficult an indirect modulation of E3 ligases, while direct inhibition strategies is limited by the somehow limited data available on E3 ligases.…”
Section: Introductionmentioning
confidence: 99%